Coupled Analysis of Thermofluid-Structure Field for Thermal Properties of Early-Age Concrete Influenced by Electric Heating System - Lin Liu; Yue Zhao; Jianyong Han; Cheng Cheng; Chaozhe Zhang (Geofluids)
When heat energy is transferred to concrete through energy conversion by an electric heating system, the overall thermal performance of the early-age concrete is affected by the local high temperature of the concrete. This, in turn, affects the accuracy of the prediction and calculation of concrete deformation. Concrete thermal physical parameter models considering the mutual influence of heat and humidity were established to clarify the influence of an electric heat tracing system on the heat transfer performance of concrete at an early age, based on the concepts of equivalent age and hydration degree. Additionally, the COMSOL numerical simulation software was used for realizing the numerical solution of concrete heat transfer. The research indicates that the degree of hydration is affected by the heating provided by the electric heat tracing system. When curing for 40 h, the degree of hydration approaches 0.82 and remains unchanged, which indicates that the hydration of cement was almost complete in less than 2 days. The specific heat value of concrete in the early stage was significantly affected by electric heat tracing. This value of concrete at a high initial temperature was larger than that at a low temperature, while the specific heat of each point in the later stage tended to be the same. The thermal conductivity was significantly affected by the local electrical heating. The higher the temperature was, the lower the thermal conductivity was, which remained stable for two days under the influence of temperature. The key contribution of this research is to provide a coupling model for concrete curing. The findings from the study also provide industry practitioners with a comprehensive guide regarding the specific applications of the electric heating system in early-age concrete curing.